2017
DOI: 10.12691/jfnr-5-12-4
|View full text |Cite
|
Sign up to set email alerts
|

DPPH Radical Scavenging Activity and Polyphenols in the Pods of 3 Common Beans

Abstract: The pods of common beans (Phaseolus vulgaris) are rich in various nutrients, and they could therefore be important parts of the human diet. In the present study, we have analyzed the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity and the contents of polyphenols, anthocyanin, vitamin C, and carotenoid in the pods of 3 varieties of common beans. French beans had the highest DPPH radical scavenging activity and polyphenol contents among the three varieties. The anthocyanin content was 3.93 mg/g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…SRB (purple) showed a higher polyphenol content and DPPH radical scavenging activity than those of SRB (black) (p<0.05). A positive correlation between the polyphenol content and DPPH radical scavenging activity for common beans has been reported by Ci et al [14]. Polyphenols from the coat and cotyledon of SRB (purple) and SRB (black) were analyzed.…”
Section: Discussionmentioning
confidence: 53%
“…SRB (purple) showed a higher polyphenol content and DPPH radical scavenging activity than those of SRB (black) (p<0.05). A positive correlation between the polyphenol content and DPPH radical scavenging activity for common beans has been reported by Ci et al [14]. Polyphenols from the coat and cotyledon of SRB (purple) and SRB (black) were analyzed.…”
Section: Discussionmentioning
confidence: 53%
“…We found positive relationship between polyphenol content and DPPH radical scavenging activity in peel, core and pulp of five pear cultivars, and the correlation coefficient was 0.98. Many studies have demonstrated that polyphenols possessed strong antioxidant activity [18,19,20].…”
Section: Dpph Radical Scavenging Activitymentioning
confidence: 99%
“…Thus, we speculate that the DPPH radical scavenging activity of these polyphenols are mainly related to non-monomeric polyphenols. Notably, we previously reported that polymeric polyphenols may possess greater antioxidant activity [16].…”
Section: Polyphenol Content Dpph Radical Scavenging Activity and Pomentioning
confidence: 99%